Preliminary results on the regulatory role of IFN-gamma and IL-10 human schistosomiasis mansoni - Sílvia ML Montenegro; Paulo J. Miranda; Frederico GC Abath; Kirte M. Teixeira; Eridan M. Coutinho; Ana LC Domingues; Luis Manuel Ley Domínguez; Joeli Brinkman; Itay Gonçalves; Siddhartha Mahanty; Alan Sher; Thomas A. Wynn (1998)
cells from Schistosomamansoni infected mice produced large amounts ofIL-10 and that this response was temporally andmechanistically linked to the downregulation of theTh1 cytokine response (A Sher et al. 1991 JImmunol 147: 2713-2716). The addition of neu-tralizing anti IL-10 mAb to the cultures resulted inan increase in IFN- g production to levels approach-ing those seen before the egg laying phase (EJPearce & A Sher 1991 Exper Parasitol 73: 110-116). Thus, it is clear from in vitro studies on theregulation of cytokine production and the obser-vation of the Th1 and Th2 profiles during S.mansoni infection in mice that Th1 and Th2 re-sponses are counter-regulatory. However, the roleof IL-10 in controlling the cytokine response maybe dependent on the immunological backgroundof the host. T Wynn et al. (1997 J Immunol 159:5014-5023) studied S. mansoni egg induced granu-loma formation and cytokine production in knock-out mice which suggested that IL-10 may play akey role in controlling the development of bothtype 1 and type 2 responses.The present study aimed to compare thecytokine pattern in acute and chronic schistoso-miasis patients and to study the contribution of IL-10 and IFN-g to the regulation of Th1 and Th2 re-sponses.The patients selected for the study presentedacute (n=7), intestinal (n=6), hepatointestinal (n=1)or hepatosplenic (n=9) schistosomiasis mansoni asdefined previously (AD Coutinho & ALCDomingues 1987 Mem Inst Oswaldo Cruz 82 : 335-337). The control group was composed of healthyBrazilian individuals.The cytokine pattern elicited in response tosoluble egg antigens (SEA) and soluble wormadult preparation (SWAP) were compared in acuteand chronic patients. In the absence of IL-10 neu-tralization, the acute patients responded to SEAand SWAP by producing significant quantities ofIFN-g when compared with the chronic patients.There was also a significant IL-10 response incells obtained from acute and chronic patients.Neutralization of IL-10 had no significant effecton the already high levels of IFN-g produced inresponse to SEA in acute patients, while IFN-gproduction was significantly high in chronic pa-tient cells, suggesting that the cytokine regula-tory mechanisms may be different in acute andchronic infection. Neutralization of IFN- g resultedin similarly increased levels of IL-10 in acute andchronic patients, while IL-4 and IL-5 were notaffected, suggesting a counter-regulatory rolebetween IFN-g and IL-10. When spleen ofhepatosplenic patients were used in the experi-ments, the results were similar to those found inperipheral blood mononuclear cells, suggestingthat there is no anatomic differences in the ex-pression of cytokines in antigen stimulated cul-tures where IL-10 was neutralized. These studiesdemonstrate that early infection with S. mansoniis associated with a significant IFN- g response andIL-10 plays an important down-regulatory role inthat response during late infection.